One minute till bedtime 60-second poems to send you off to sleep - Nesbitt, Kenn; Niemann, Christoph (New York Boston Little, Brown and Company, 2016)
Book of bedtime poetry.
How to fall asleep / Kenn Nesbitt -- Gran's visit / Sally Murphy -- Setting the table / Jane Yolen -- No peas / Teena Raffa-Mulligan -- Canoe / Juanita Havill -- How to live forever / Judith Viorst -- While I am asleep in my bed / Michael Salinger -- Air ships / Charles Ghigna -- Morning star / Jackie Hosking -- Night flight / Ted Scheu -- Moon mice / Neal Levin -- Meeting a cow / Sharon Creech -- Old Ned / David Davis -- Armadillo / David Davis -- For Pete's snake / Linda Knaus -- My friend the chameleon / Nina Laden -- Sandra's pet / Martin Pierce -- Rock Pool / Matt Goodfellow -- I dreamed I met a unicorn / Dave Crawley -- Last poem / Stephanie Calmenson.
Elementary Grade
104769
Keywords: Poetry; Children's poetry; Juvenile works